From popular education to decolonizing thought in Paulo Freire: From popular education to decolonizing thought in Paulo Freire - MORÁN BELTRÁN, Lino; TORRES DÍAZ, Gabriel; MIRANDA SAMPER, Orlando (Utopía y Praxis Latinoamericana, 2021)
This text, based on critical analysis, belongs to the History of Ideas in our America. Its objective is to underline in Paulo Freire’s work the relation that exists among his concept of popular education and decolonizing thought. As a result, we can conclude that his work is dedicated to liberation, and that includes all the efforts to build a more just and fair society. His project of pedagogy of the oppressed, based on the perspective of popular education, sinks its arguments in a critique of capitalist society and its rationality, which promotes an educative model to justify the dichotomy oppressor-oppressed, colonizer-colonized.